Automatic detection temperature transmitter for calibration process using thermocouple - Muhamad Farid, A. Wahab (2010)
The purpose of this project is to detect temperature for calibration process using type K thermocouple automatically. This project will be implementing using Visual Basic 2008 software to develop Graphic User Interface (GUI). The Type K thermocouple will be use as temperature sensor in calibration process. The implementation of proportional–integral–derivative controller (PID controller) will be monitor the automatic temperature set point and detection system. The Data Acquisition (DAQ) card will be use for interfacing process is to implementation of an automatic detection system for temperature measuring during calibration process. The accuracy of the measurement will be monitor besides the analysis of uncertainty and confidence limit